The Effect Of Multiball Training On The Precision Of Forehand Button In Table Tennis Extracurricular Students Of Sma Negeri 7 Bengkulu City - Alexon Alexon; Defliyanto Defliyanto; Dian Pujianto; Ari Sutisyana; Angga Burlian (UNIB Press, 2021)
This study aims to determine the effect of multiball training on forehand accuracy in table tennis extracurricular students. This research was conducted at SMA Negeri 7 Bengkulu City. In this study using a Quasi experimental method (quasi experimental). The design used was one group pretest posttest design, that is, pretest was done before treatment and posttest was done after treatment. The treatment given was multiball training with various variations. This design requires a group without comparison. The population in this study amounted to 16 students, the sample selection used a total sampling technique where the entire population was taken as the research sample. The data collection technique in this study was the direct test method, namely using the 1x pretest, 14x trials and 1x posttest in table tennis. The statistical prerequisite test fulfills the requirements that the data is normally distributed based on statistical counts. The results obtained from the data t count 142.13 and t table 2.13145 with a level of = 0.05. The results of this study indicate that there is an effect of multiball training on forehand accuracy in table tennis extracurricular students at SMA Negeri 7 Bengkulu City, so it can be concluded that multiball training affects the improvement of forehand accuracy in table tennis extracurricular students.